Pengembangan Instrumen Kecemasan Belajar Fisika bagi Siswa SMA - Isran Mihardi; Supahar (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2026)
Physics learning anxiety is an affective factor that can influence students’ readiness to learn, concentration, and academic achievement. This study aimed to develop a valid and reliable instrument to measure physics learning anxiety among senior high school students. The development procedure followed the stages of research and development (R&D), including preliminary study, construction of dimensions and indicators, item development, content validation by five experts, limited trial testing (N = 30), and large-scale testing (N = 150). Content validity was analyzed using the Content Validity Ratio (CVR) and Content Validity Index (CVI). Empirical validity was determined through corrected item–total correlation (r_it), while reliability was assessed using Cronbach’s Alpha. The results showed that the instrument demonstrated strong content validity, indicated by a high CVI value. Empirical testing revealed three items (25, 34, and 37) that did not meet the r_it ≥ 0.30 criterion and were therefore removed. The final instrument consisted of 37 items with very high reliability (α = 0.939). This instrument is suitable for use as a measurement tool for assessing physics learning anxiety among senior high school students.